Imperial Confusion: America's Post-colonial and Post-revolutionary Empire. Issue 3 (4th May 2021) - Griffin, Patrick
ABSTRACT: This essay explores the question of whether we should consider the newly-independent United States an 'empire.' It does so by discussing emerging schools of thought that have suggested that the post-revolutionary state was more powerful than we had previously reckoned, as well as those that argue that the new state, though efficacious, is best considered post-colonial in its international standing and in its fit in a global political economy. To reconcile these positions, to tie the post-revolutionary to the post-colonial, we would be wise to look around the Atlantic and consider how what was happening in the United States was not exceptional during the broader Age of Revolution. The United States, like others, had to be an expansive state – even if the word 'empire' does not fit its case perfectly – to address its continuing colonial status stemming from independence and the dilemmas created by revolution.